Peralihan Moda Transportasi Jasa Pengiriman Menggunakan Metode Analytical Hierarchy Process (AHP): Studi Kasus PT. XYZ - Yuliyani Nur Angraini; Meilani Rosita; Amalia Ananda Putri Taufiq (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
PT XYZ is the cargo company that had operate along Surabaya-Solo-Jakarta rute. This company opeated the bussiness by a traditional carrier that only used truck as a transportation mode. The company decision to used this mode because of its had any strengthen like the easyness of locations access and the more delivery frequency. But in its operations also had any weakness like the problem of time, quality and cost. The frequent problem is about the losses because of the cost of delivery is more than its benefit. So that, its required to changed the transportation mode to solved this losses. The changed of transportation mode that can be applicated is the used of train. We used an Analytical Hierarchy Process (AHP) to make decision about the best alternative in this problem. From the equation we have a percentage of the used of train can solved this problem 53% more than the used truck.